Life at the Margins: Regional Inequality in Tunisia and International Migration - Belhadj, Hiba (AUC Knowledge Fountain, 2023)
Drawing on De Haas’s (2021) argument on migration as a function of people’s aspirations and capabilities, this research examines how regional inequality in Tunisia – affecting both aspirations and capabilities – impacts and shapes the opportunities and outcomes of migration. Building on De Haas’s migration typology, this research will argue that people from marginalized regions undertake “precarious migration.” For this group of migrants, precarity is employed to explain not only their migration but also their employment and livelihood conditions at home. Those from developed regions undertake “free” or “improvement” migration. In a further step, the research examines how these different migrant categories perpetuate beyond the Tunisian borders: observing their continuity through European structural conditions. Because of the focus on attracting highly skilled migrants and the segmented labor market, the inequality between the two groups is assumed to be sustained as they leave, arrive, and work on adverse terms. Hence, the concept of precarity, characterized by inequality, insecurity, and uncertainty, re-emerges to explain the situation of Tunisian migrants from marginalized regions in their destination country. The focus will be on France, the primary destination of Tunisian migrants.